Fiesta, local identity and symbolic exaltation of utopia. The Mad from Fuente Carreteros - Gustavo Ramirez (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2018)
The festive ritual around the dance of «Los Locos de Fuente Carreteros», in Cordoba province, makes up an ingrained expression of local identity and a popular exaltation of the utopia which, at the same time, reflects the inner cultural diversity in Andalusia. Introduced by the Central European colonists in the second half of the 18 th century, According to the MOST Widespread belief, it is held every 28 th of December With An Important social participation and careful zeal for keeping and transmitting the tradition. After intense arrangements since the day before, with special devotion from some groups of women, «los locos» meet in the square, perform the dances and, then, go across some streets in the village. «La Danza del Oso» (the dance of the bear), the tasting of «pestiños» (sweet Spanish fritters) and cups of anisette and a popular lunch complete the celebration.